The Covid-19 pandemic within a global linguistic landscape: A comparative case study - Mitits, Lydia (Aegean Working Papers in Ethnographic Linguistics, 2022)
The Covid-19 pandemic has affected all aspects of our lives profusely and irreversibly and has changed the way we experience public spaces. This study aims at portraying instances of linguistic landscapes (LLs) of the pandemic by comparing three very different cities, a provincial Greek town, a developing city in Serbia, and a world metropolis in the U.S. Due to restricted mobility and limited possibilities to carry out fieldwork, the photographic data have been collected by the researcher and trained informants, followed by interviews about opinions/impressions of Covid-19 related language in public spaces. The results show that the three LLs share the expected universal characteristics but also reflect different political, socioeconomic, and cultural idiosyncrasies. My findings also show that (a) LLs seem to lag behind other sources when sharing information and communicating meanings and (b) we appear to rely less on them to guide us as we navigate our cities.